The great frozen sea [electronic resource] : a personal narrative of the voyage of the "Alert" during the Arctic expedition of 1875-6 - Markham, Albert Hastings, Sir, 1841-1918. (London : K. Paul, Trench, Trübner, 1894)
'"There's a flag on the mast . "--Frithiof's "Saga".' Includes index. Electronic reproduction. Mode of access: Internet. 44